Karakteristik Profil Jaringan Lunak pada Penderita Obstruksi Saluran Napas Atas dengan Kebiasaan Bernapas Melalui Mulut - Erly Budianto; Miesje Karmiati Purwanegara; Erwin Siregar (Faculty of Dentistry, Universitas Indonesia, 2013)
Obstruction of the upper respiratory tract (OURT) will cause mouth breathing that is known to influence neuromuscular activity. This will lead to malformation of face growth pattern and head posture that can result in dentocraniofacial deformity. This research aimed to identify the differences in soft tissue profile characteristics in OURT patients compared to normal subjects, and to analyze the differences between boys and girls in this respect. An analytic descriptive study with cross sectional design was applied. The sample consists of 96 subjects including 64 OURT patients (32 boys and 32 girls) and 32 normal subjects (11 boys and 21 girls). The results showed that the OURT patients had convex profile and longer distance than the normal subjects between upper or lower lip to esthetic line (p<0.05). Furthermore, normal male subjects had longer distance of upper lip to E-line than females (p=0.039). The same was also shown in OURT patients, i.e. male patients had longer distance of upper and lower lip to E-line compared to females (p<0.05). DOI: 10.14693/jdi.v15i1.83